Upaya Meningkatkan Kedisiplinan Guru Masuk Kelas Dalam Mengajar Pasca Pandemi Melalui Penerapan Reward And Punishment Di SMK N 4 Rambah - Yulisman Yulisman (STKIP ROKANIA, 2022)
This research was motivated by the lack of discipline of teachers coming to school after the Covid-19 pandemic. The aim of the researcher is to find alternative problem solving as an effort to improve teacher discipline in teaching attendance in class through the application of reward and punishment. The method in this study is the School Action Research (PTS) method with two cycles, the subjects of this school action research are the teachers at SMK N 4 Rambah with a total of 29 people. Based on data analysis, it can be seen that the arrival of teachers in schools has increased from the previous cycle. On average, teachers come before 07.00 an average of 16-20 people, who come after 07.00 an average of 9-13 people. This indicates that there has been an increase in teacher arrivals in cycle II by applying rewards and punishments